PENGELOLAAN SAMPAH, TINJAUAN KEBIJAKAN - SILAHUDIN, SILAHUDIN; Lestari, Sri (Jurnal Sosio dan Humaniora (SOMA), 2025)
AbstractThe waste problem has become a problem, because its volume can exceed the population faced by many regions/cities in Indonesia. Therefore, its management is a strategic challenge in Sustainable Development,The purpose of this study is to highlight waste management policies in Indonesia with a focus on effectiveness, implementation challenges, and sustainable policy directions.The research methodology uses a qualitative descriptive approach through data collection through documentation studies of national regulations or policies.The results of the study, there are findings that show that various regulations such as Law No. 18 of 2008 concerning Waste Management, and Presidential Regulation No. 97 of 2017 concerning National Policy and Strategy (Jakstranas) for Waste Management, however, their implementation still faces various obstacles, including weak coordination between institutions, budget constraints, and suboptimal community participation.Therefore, the recommendation is that a policy reformulation is needed based on a circular economy approach, multi-party participation, and strengthening regional institutions.Keywords: Public Policy, Waste Management, Circular Economy, Community Participation